Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.cgd.9b01225
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Crystallization Interrupted with Competing Binding Agents

Abstract: Uric acid crystallization in humans is associated with undesirable medical conditions including the formation of gout deposits and kidney stones. A major contributing factor to uric acid biomineralization, most often as either monosodium urate (MSU) or anhydrous uric acid (UA), is its relatively low solubility in physiologic solutions. Using bidentate and tridentate binding patterns designed to disrupt the binding motifs observed in the major physiologic forms, several heterocycles were identified which (1) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…When its concentration exceeds the solubilizing capacity of physiologic fluid, it can precipitate in a variety of hydrated, , anhydrous, and salt forms, which are the undesirable manifestations of gout and kidney stone formation. In large-scale studies of kidney stone composition, uric acid is most commonly found in anhydrate (UA) and dihydrate (UAD) forms. Previous work has shown that although the dihydrate (UAD) precipitates rapidly from supersaturated aqueous solutions, , over time it can eventually transform to the more stable and less soluble UA via a dissolution–recrystallization process. , In the course of studies focused on identifying additives that might interrupt uric acid crystallization, we found that the addition of substoichiometric quantities of 2,4-diaminopyrimidine to the growth solution yielded UAD crystals with altered morphologies which transform via a highly unusual mechanism.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…When its concentration exceeds the solubilizing capacity of physiologic fluid, it can precipitate in a variety of hydrated, , anhydrous, and salt forms, which are the undesirable manifestations of gout and kidney stone formation. In large-scale studies of kidney stone composition, uric acid is most commonly found in anhydrate (UA) and dihydrate (UAD) forms. Previous work has shown that although the dihydrate (UAD) precipitates rapidly from supersaturated aqueous solutions, , over time it can eventually transform to the more stable and less soluble UA via a dissolution–recrystallization process. , In the course of studies focused on identifying additives that might interrupt uric acid crystallization, we found that the addition of substoichiometric quantities of 2,4-diaminopyrimidine to the growth solution yielded UAD crystals with altered morphologies which transform via a highly unusual mechanism.…”
mentioning
confidence: 82%
“…It was known from previous studies that 2,4-diaminopyrimidine (24-DAP) and some of its derivatives can cocrystallize with uric acid in 1:1 ratios. 16 In our experience, cocrystallization required that solutions contain equimolar or higher ratios of uric acid and 24-DAP; solutions with lower concentrations of 24-DAP yielded only UAD. On closer inspection, we observed that the morphologies of the UAD crystals grown in the presence of these substoichiometric 24-DAP concentrations were clearly altered compared to those obtained from pure aqueous solution.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The UA–Mel complex has a nonplanar structure that conforms to the most stable structure, as stabilized by several H-bonding interactions . π-Stacking is accountable for the self-association of UA. , Therefore, significant π-stacking interactions, together with multiple associations with hydrogen bonding, inevitably play a very vital and perhaps decisive role in the Mel and UA assembly and thus implies a high complexity . A straightforward yet realistic approach may indeed entail either devastation of UA aggregation or an impediment of a Mel and UA hydrogen-bonded cluster.…”
Section: Introductionmentioning
confidence: 99%